Nitrogen fertilization coupled with foliar application of iron and molybdenum improves shade tolerance of soybean under maize-soybean intercropping - Nasar, Jamal; Wang, Gui Yang; Zhou, Feng Jue; Gitari, Harun; Zhou, Xun Bo; Tabl, Karim M.; Hasan, Mohamed E.; Ali, Habib; Waqas, Muhammad Mohsin; Ali, Izhar; Jahan, Mohammad Shah (Frontiers in Plant Science, 2022)
Maize-soybean intercropping is practiced worldwide because of some of the anticipated advantages such as high crop yield and better utilization of resources (i.e., water, light, nutrients and land). However, the shade of the maize crop has a detrimental effect on the growth and yield of soybean under the maize-soybean intercropping system. Hence, this experiment was conducted to improve the shade tolerance of such soybean crops with optimal nitrogen (N) fertilization combined with foliar application of iron (Fe) and molybdenum (Mo). The treatments comprised five (5) maize-soybean intercropping practices: without fertilizer application (F0), with N fertilizer application (F1), with N fertilizer combined with foliar application of Fe (F2), with N fertilizer coupled with foliar application of Mo (F3) and with N fertilizer combined with foliar application of Fe and Mo (F4). The findings of this study showed that maize-soybean intercropping under F4 treatment had significantly (p < 0.05) increased growth indices such as leaf area (cm2), plant height (cm), stem diameter (mm), stem strength (g pot-1), and internode length (cm) and yield indices (i.e., No of pods plant-1, grain yield (g plant-1), 100-grain weight (g), and biomass dry matter (g plant-1)) of the soybean crop. Moreover, intercropping under F4 treatment enhanced the chlorophyll SPAD values by 26% and photosynthetic activities such as Pn by 30%, gs by 28%, and Tr by 28% of the soybean crops, but reduced its CO2 by 11%. Furthermore, maize-soybean intercropping under F4 treatment showed improved efficiency of leaf chlorophyll florescence parameters of soybean crops such as Fv/Fm (26%), qp (17%), ɸPSII (20%), and ETR (17%), but reduced NPQ (12%). In addition, the rubisco activity and soluble protein content of the soybean crop increased by 18% in maize-soybean intercropping under F4 treatment. Thus, this suggested that intercropping under optimal N fertilization combined with foliar application of Fe and Mo can improve the shade tolerance of soybean crops by regulating their chlorophyll content, photosynthetic activities, and the associated enzymes, thereby enhancing their yield and yield traits.